2023
DOI: 10.1007/s00330-023-09599-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of R2* with fat fraction and bone mineral density and its role in quantitative assessment of osteoporosis

Abstract: Objectives To investigate the correlation of R2* with vertebral fat fraction (FF) and bone mineral density (BMD), and to explore its role in the quantitative assessment of osteoporosis (OP). Methods A total of 83 patients with low back pain (59.77 ± 7.46 years, 30 males) were enrolled, which underwent lumbar MRI in IDEAL-IQ sequences and quantitative computed tomography (QCT) scanning within 48h. The FF, R2*, and BMD of all 415 lumbar vertebrae were respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Liu et al investigated the quantitative MRI assessment of 83 patients with low back pain-results showed that R2* had a lower AUC than FF in diagnosing the progression of osteoporosis and osteopenia, making it difficult to use it as an independent diagnostic indicator for osteoporosis. 38 Leonhardt et al showed average change of FF was significantly higher in patients developing incidental fractures than those without fractures, while T2* showed no significant changes. 39 In this study population, T2* was not independently associated with HRMM.…”
Section: Discussionmentioning
confidence: 95%
“…Liu et al investigated the quantitative MRI assessment of 83 patients with low back pain-results showed that R2* had a lower AUC than FF in diagnosing the progression of osteoporosis and osteopenia, making it difficult to use it as an independent diagnostic indicator for osteoporosis. 38 Leonhardt et al showed average change of FF was significantly higher in patients developing incidental fractures than those without fractures, while T2* showed no significant changes. 39 In this study population, T2* was not independently associated with HRMM.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, level-specific vertebrae not only differ in the related incidence of VFs but also present disparities in intrinsic characteristics, such as BMD and fat fraction [18,32,33]. These intrinsic characteristics have been established to be associated with osteoporotic fractures and can assist with the identification of such fractures [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 36 ] found a moderately positive correlation between R2* and BMD in postmenopausal women, with the area under the curve (AUC) of 0.821, 0.784 and 0.922 for FF, R2* and FF combined with R2* for the diagnosis of osteoporosis. Liu et al [ 37 ] found that R2 * value was weakly associated with FF and BMD ( r = -0.219, 0.290, P < 0.05), and the diagnostic efficacy of R2 * in diagnosing osteoporosis was relatively poor. Kim et al [ 38 ] selected L4 vertebra to measure FF and R2* value and found that R2* correlated more significantly with BMD in women than in men, with higher AUCs for FF in men and R2* in women when predicting osteopenia and osteoporosis.The different results of different studies may be due to a variety of reasons including variability in the included participants, inconsistency in the range of vertebrae studied, and differences in the scanning protocols.…”
Section: Discussionmentioning
confidence: 99%